Overcoming the jobs-versus-environment dilemma: A feminist analysis of the foundational economy - Sonia Kuhls (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
This paper examines the potential of the foundational economy as an industrial policy strategy for addressing the challenges posed by the socio-ecological transformation. Grounded in Marxist and feminist theories, the analysis sets out to deconstruct the jobs-versus-environment dilemma, revealing that dignified employment and climate mitigation are jointly imperiled by the capitalist mode of production. Nonetheless, ambitious environmental policies will necessitate structural economic changes and hence labor reallocations. In this context, the paper seeks to establish links between the foundational economy concept - which is primarily concerned with economic development and industrial policy - and sustainability research. I contend that the foundational economy emerges as a promising avenue for addressing potential adverse effects of the socio-ecological transformation for two main reasons. First, it serves as a practical guide for necessary labor reallocations, proposing the absorption of workers into low-carbon, welfare-oriented sectors. Second, it functions as a discursive strategy that directly engages with workers'self-perception and concerns, prioritizing community health and offering socially sustainable and meaningful employment. Despite these merits, the paper underscores the need for the foundational economy to address feminist critiques of labor and unpaid social reproduction to fully unlock its transformative potential. Additionally, the role of trade unions in supporting and shaping the foundational economy warrants further investigation, urging future research to delineate the positionality and strategies of trade unionsin the consolidation of this economic approach.
Keywords: B51; B54; J21; J51; L52; Q56; Q57; 330; employment; foundational economy; industrial policy; social reproduction; socio-ecological transformation; trade unions